ASUHAN KEBIDANAN PADA IBU NIFAS DENGAN KONSTIPASI DAN FAKTOR YANG MELATARBELAKANGI Care Midwifery Of In Post Partum Mothers With Constipation And Background Factor - Agustin Dwi Syalfina; Sari Priyanti; Nafisatul Maula (MEDICA MAJAPAHIT, 2019)
Postpartum is the period of a mother who starts from the placenta to 6 weeks postpartum (42 days). The postpartum period is important for monitoring by midwives because many complained of discomfort during the post partum may even lead to complications such as post-partum infection. Maternal morbidity during puerperium is one of the highest causes in the prevalence of maternal mortality. Physical and psychological complaints that occur during the puerperium are things that must be a concern and become pathological if not done properly. Physical discomfort appears on puerperium including perineal pain due to trauma or injury sectio cesarean delivery, back pain, constipation, hemorrhoids, urinary incontinence, fecal incontinence, and exhaustion. The discomfort of the puerperium that is often experienced by the mother is constipation. Constipation in the puerperium occurs because of pain in the perineum and fear if there is pressure on the anus when defecation will affect the healing of perineal wounds, drug anesthesia, the influence of the hormone progesterone, dietary restrictions, lack of mobilization and psychological factors. Constipation causes the complications of hemorrhoids, post partum infection and bowel cancer if it is not done fast and precise management. Management given to postpartum mothers with constipation includes recommending consumption of fruits and vegetables such as plantains, papaya not only rice and side dishes, recommending morning walks and teaching postpartum exercise, telling mothers to consume 8 liters of water per day and collaborating with doctors for giving therapy.